Revisiting Michael C. Jensen’s Three Principles for Great Leadership: A Critical Appraisal in Islamic Educational Leadership - Minhaji; Akhsan; Mahmudi; Supriadi; Rif’ah; Nurainun (Mimbar Agama Budaya, 2025)
This study aims to examine in depth the three basic principles of leadership: integrity, Authenticity, and commitment to something greater than oneself as foundational elements of effective leadership within the context of Islamic education. These principles are not only moral guidelines but also ethical and existential frameworks that shape a leader’s character and behavior. This research employs a qualitative research design with an interpretive approach. Data were collected through in-depth interviews with Islamic education leaders (kiai, school principals, and senior teachers), participant observation in selected Islamic educational institutions, and document analysis of leadership texts and institutional policy documents. The data were analyzed using thematic analysis to identify recurring patterns and meanings embedded in leadership practices within Islamic educational settings. The findings reveal that integrity serves as the core pillar that establishes public trust in leaders. Authenticity plays a crucial role in sustaining moral consistency and personal honesty. At the same time, a commitment to a purpose beyond oneself motivates leaders to act in the collective good rather than their own self-interest. In the context of Islamic education, these principles align strongly with the values of amanah, siddiq, and khidmah, which characterize the leadership exemplified by the Prophet Muhammad SAW. This study concludes that the three principles are not only compatible with modern leadership theories but are also universal and highly relevant to the development of Islamic educational leadership. The study implies the need to develop leadership training programs in Islamic education that emphasize character formation and leadership ethics based on these three core principles.